HUBUNGAN HYGIENE SANITASI DENGAN KEBERADAAN BAKTERI ESCHERICHIA COLI PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DIKECAMATAN CIMANUK DAN CIPEUCANG KABUPATEN PANDEGLANG 2020 - Sasmita, Heny; Somantri, Ucu Wandi; Nurkhalizah, Elisya Siti; Ariyadi, Bambang (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Refill Drinking Water Depot (DAMIU) is one of the industrial businesses where the production is processing raw water so that it becomes drinking water suitable for consumption by various people by refilling in a place that we often know as refill depots. The purpose of this study was to determine the relationship between sanitation hygiene and the presence of Escherichia coli bacteria in refill drinking water depots in Cimanuk and Cipeucang Districts in 2020. Methods: This was a cross sectional studies with a total of 30 samples of refillable drinking water depots were collected to determine the presence of E. coli bacteria.. Results: Result showed that the depots that did not meet the hygiene sanitation requirements of the place, tools and handlers were 83.3% depots, 40% depots and 80% respectively. Escherichia coli bacteria were found in 18 samples 60%. There was no relationship between the hygiene sanitation conditions of the place with the presence of Escherichia coli bacteria. Relationship was found between the condition of hygiene and sanitation tools with the presence of Escherichia coli bacteria, obtained p = 0.007 (p <0.05). The relationship between handler hygiene conditions and the presence of Escherichia coli bacteria was obtained p = 0.026 (p <0.05). Conclusion: A significant relationship was found between the hygiene sanitation conditions of the appliance and the hygiene conditions of the handlers with the presence of Escherichia coli bacteria in refill drinking water depots in Cimanuk and Cipecang Districts.